GUITAR TEACHING: STATE OF THE ART AND RESEARCH QUESTIONS - Gómez-Ullate García de León, Martín (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This work reviews guitar methodologies and didactic materials from the first 16th century methods of guitar and vihuela to the software/hardware devices patented now-a-days. One of the richest sources for guitar education research are master classes registered since the last 50-100 years and available today to the researcher. A set of 12 master classes are analysed in this study. Fundamental decisions for the education and practice of the guitar are highlighted as the fingernails vs. yolks playing, “learning by music” vs. “learning by ear”, the use of music vs. tablature notation or the autodidactic way vs. the teacher-student interaction in class. Despite the successful new devices and advances in software and hardware, literature review reveals the importance of the teacher and the classical methods.